The Sovietization of Creative Writing in Romania. The Role of the Mihai Eminescu School of Literature and Literary Criticism (1950–1955) - Balázs Imre József (Hungarian Studies Yearbook, 2020)
Within the paradigm of socialist realism, one of the means of introducing new models of producing literature in Romania and other neighbouring countries was the Soviet idea and practice of literary training. In the Romanian context, the Mihai Eminescu School of Literature and Literary Criticism from Bucharest was intended to produce the new, young generation of writers that would articulate the new system of values. Reports about the School show that the social origin of the students was carefully monitorized, and ethnic diversity also played a role in the process of the sovietization of the whole Romanian literary field. The personal level of experiencing the cultural and political practice of the School shows the possibilities and also the limitations of the project. The paper examines the history of the School through official party documents and also personal accounts, in order to analyze the particular strategies and also the difficulties of adapting certain Soviet institutional models within the Romanian context.